The hydrostatic control of load-induced height changes above subglacial Lake Vostok. Issue 271 (11th October 2022) - Richter, Andreas; Schröder, Ludwig; Scheinert, Mirko; Popov, Sergey V.; Groh, Andreas; Willen, Matthias; Horwath, Martin; Dietrich, Reinhard
Abstract: Lake Vostok, East Antarctica, represents an extensive water surface at the base of the ice sheet. Snow, ice and atmospheric pressure loads applied anywhere within the lake area produce a hydrostatic response, involving deformations of the ice surface, ice–water interface and particle horizons. A modelling scheme is developed to derive height changes of these surfaces for a given load pattern. It is applied to a series of load scenarios, and predictions based on load fields derived from a regional climate model are compared to observational datasets. Our results show that surface height changes due to snow-buildup anomalies are damped over the lake area, reducing the spatial standard deviation by one-third. The response to air pressure variations, in turn, adds surface height variability. Atmospheric pressure loads may produce height changes of up to $±$ 4 cm at daily resolution, but decay rapidly with integration time. The hydrostatic load response has no significant impact neither on ICESat laser campaign biases determined over the lake area nor on vertical particle movements derived from GNSS observations.